THE IMPLEMENTATION OF TBLT TO ENHANCE STUDENTS’ WRITING ACHIEVEMENT - Angga Ari S; Diyah Atiek Mustikawati; Risqi Ekanti A.P (Universitas Muhammadiyah Ponorogo, 2020)
The researcher encountered several problems in understanding writing in SMPN 1 Siman. Such as, students think that writing is a boring activity. The students feel that English is difficult to learn. The objective of this research study is to find out the implementation of task-based language teaching strategies (TBLT) to enhance writing achievement at SMPN 1 Siman in the academic year of 2019/2020. The subject of this research was the students of eighth grade of SMPN 1 Siman in academic year of 2019/2020, which is consisted 24 students. This classroom action research was conducted in two cycles. The researcher used three research instruments. They were observation checklist, questionnaire, and test.Based on the result of this research, the implementation of TBLT to enhance students’ writing achievement at SMPN 1 Siman. The result of observation checklist showed that the students became active during teaching learning process. It was seen from the result of observation checklist cycle 1 was 72% in cycle 2 was 80%. The result of questionnaire showed that the students more get motivation with this strategy. It was seen from the resullt in cycle 1 was 66,7% and the cycle 22 was 75,1%. The test in cycle 1 showed that there were 68.8% who got low score under basic minimum standard was 75. Then in cycle 2, who reached the minimum score based from KKM was 77,8% the researcher conclude that the result from observation, questionnaiire, and thest in cycle 2 is better than cycle 1. It meant that the study had been succesful by using TBLT strategy.Finnaly, the researcher give suggestion for English teachers, students, and further researcher can use TBLT (task-based language teaching) strategy as alternative strategy in teaching writing. The next researcher can develop this strategy by using various media to get the better result in teaching learning process. Key Word: TBLT strategy, Writing